Hard carbons from waste hemp via hydrothermal carbonization with mil chemical activation for sodium–ion batteries - Antoran Navarro, Daniel; Alvira, Darío; Manyà, Joan J. (Jornada de Jóvenes Investigadores del I3A, 2023)
Owing to its wide availability and low cost, sodium-ion batteries (SIBs) appear as a very promising option for post-lithium energy storage systems. However, commercial graphite anodes used in lithium-ion batteries are not suitable for SIBs, due to a difficult insertion of sodium ions into the graphitic layers. Possible anode candidates focus on hard carbons (HCs). Here, HCs were synthesized from waste hemp hurd (WHH) via hydrothermal pretreatment (with either heteroatom doping or K2CO3 activation) and subsequent carbonization under Ar at 800 or 1000 °C. Regarding mild chemically activated HCs, the best material (exhibiting a 76% ICE and impressive reversible charge capacities of 354 and 77 mA h g–1 at 0.1 and 2 A g–1, respectively) was the carbon produced via hydrothermal preatretment in HCl aqueous solution and subsequently heated up to 1000 °C. However, poor cycling stability was observed for the last material, suggesting that some irreversible sodiation processes can take place.